Relationship between Knowledge, Attitudes, and Motivation and Compliance to Taking Anti-Tuberculosis Medication on the Pulmonary TB Patient - Dewi - Aryanti; Syaukia Adini; Novi Indriani (Jurnal Keperawatan Respati Yogyakarta, 2023)
Tuberculosis (TB) is a deadly infectious disease worldwide. The annual number of global TB sufferers seeking treatment has increased from around 6 million people in 2015 to 7.1 million people in 2019. Geographically, most TB cases occurred in the Southeast Asian region, one of which is Indonesia. Many factors affect the success and compliance with treatment programs, including knowledge, attitudes, perceptions, and individual motivation. Increased knowledge can lead to changes in one's perceptions, attitudes, or habits. This research contribution analyzes the relationship between knowledge, attitudes, and motivation with compliance to taking anti-tuberculosis medication in pulmonary TB patients at RSUD Dr. Soekardjo, Tasikmalaya City. Furthermore, this research is a descriptive analytical-correlational research with a cross-sectional approach. The sample of this study was 60 respondents (aged 20-80 years) consisting of outpatients at the TB Polyclinic at RSUD Dr. Soekardjo in October-November 2022. The instrument used to measure the variables of knowledge, attitudes, motivation, and medication compliance is a questionnaire. The relationship between the variables was carried out using the Chi-Square statistical test. Based on the research results, it was obtained that 95% (57) of the respondents had good knowledge, 73% (44) of the respondents had good attitude, 72% (43) had good motivation, and 51.7% (31) of the respondents were adherent in taking medication. Furthermore, based on the results of statistical analysis using the Chi-Square test it showed that attitude and motivation variables were not significantly related to medication compliance (p-value >0.05), while the level of knowledge was significantly related to medication compliance (p-value < 0.05). It was further concluded that the level of knowledge of the respondents shows a significant relationship with compliance to taking OAT medication at Dr. Sukarno Hospital.